Incidence and risk factors for clinical neurodegenerative Langerhans cell histiocytosis: a longitudinal cohort study. (12th November 2018) - Héritier, Sébastien; Barkaoui, Mohamed‐Aziz; Miron, Jean; Thomas, Caroline; Moshous, Despina; Lambilliotte, Anne; Mazingue, Françoise; Kebaili, Kamila; Jeziorski, Eric; Plat, Geneviève; Aladjidi, Nathalie; Pacquement, Hélène; et al.
Abstract: Neurodegenerative (ND) complications in Langerhans cell histiocytosis (LCH) are a late‐onset but dramatic sequelae for which incidence and risk factors are not well defined. Based on a national prospective registry of paediatric LCH patients, we determined the incidence rate of clinical ND LCH (cND‐LCH) and analysed risk factors, taking into account disease extent and molecular characteristics. Among 1897 LCH patients, 36 (1·9%) were diagnosed with a cND‐LCH. The 10‐year cumulative incidence of cND‐LCH was 4·1%. cND‐LCH typically affected patients previously treated for a multisystem, risk organ–negative LCH, represented in 69·4% of cND‐LCH cases. Pituitary gland, skin and base skull/orbit bone lesions were more frequent ( P < 0·001) in cND‐LCH patients compared to those without cND‐LCH (respectively 86·1% vs. 12·2%, 75·0% vs. 34·2%, and 63·9% vs. 28·4%). The 'cND susceptible patients' ( n = 671) i.e., children who had experienced LCH disease with pituitary or skull base or orbit bone involvement, had a 10‐year cND risk of 7·8% vs. 0% for patients who did not meet these criteria. Finally, BRAF V 600E status added important information among these cND susceptible patients, with the 10‐year cND risk of 33·1% if a BRAF V 600E mutation was present compared to 2·9% if it was absent ( P = 0·002).